PENERAPAN STRATEGI KREATIF DALAM PEMBUATAN VIDEO PROMOSI PROGRAM LOYALITAS DI PT SUCOR SEKURITAS - Damaiyanti, Alfina; Suwanda, Bayu Suriaatmaja; Ernawati, Erna (Fakultas Ilmu Dakwah dan Komunikasi, 2024)
Audio-visual media that can be used by a company to inform a product or brand is a promotional video. The goal of conveying messages that be attractive and easily understood by the audience in promotional videos requires a creative strategy. Sucor Sekuritas is a company that conducts business activities as a securities broker, and securities underwriter supervised by the Financial Services Authority (OJK). Efforts to maintain and generate a sense of trust and loyalty are generated through a special loyalty program for Sucor Sekuritas. The loyalty program is run on a business-to-business (B2B) basis with merchants to provide a discount or special service for Sucor Sekuritas customers. Information about the Sucor Sekuritas loyalty program needs to be expanded with the use of promotional video media with an informative creative strategy and supporting elements in the promotional video. This research aims to explain the implementation of creative strategies in Sucor Sekuritas' promotional videos using theories from Gilson and Berkman and Handes. This research uses primary, and secondary data and instruments relevant to creative strategies.